Determination of anthocyanins in cherry and cranberry by high-performance liquid chromatography-electrospray ionization-mass spectrometry - Karaaslan, Nagihan M.; Yaman, Mehmet (Springer, 2016)
Anthocyanins are a group of widespread natural phenolic compounds in vegetables and fruits. The anthocyanins have a wide range of applications due to the antioxidant, anticancer and anti-inflammatory properties. In this study, anthocyanins (delphinidin-3-o-glucoside, cyanidin-3-o-glucoside, pelargonidin-3-o-glucoside and malvidin-3-o-glucoside) in cherry and cranberry were determined using high-performance liquid chromatography-electrospray ionization-mass spectrometry (HPLC-ESI-MS). The anthocyanins were separated using gradient elution and a reserved-phase analytical column before identification by high-performance liquid chromatography-electrospray ionization-mass spectrometry. A high-performance liquid chromatography-electrospray ionization-mass spectrometry method was optimized for the determination of anthocyanins in cherry and cranberry. Furthermore, in this study, we investigated extraction conditions of fruit samples as well as determination of optimum HPLC-ESI-MS conditions. This study is novel in terms of simultaneously examining both optimization of HPLC parameters and extraction conditions. Obtained optimum conditions were used for the determination as the quantitative and qualitative analysis of anthocyanins in cherry and cranberry. The content of anthocyanins on the basis of wet weight in cherry and cranberry samples was determined for delphinidin-3-o-glucoside < d.l. (detection limit) and < d.l., for cyanidin-3-o-glucoside varied from 3.5 +/- A 0.4 to 8.3 +/- A 1.1 mg kg(-1) (average 5.8 +/- A 0.8 mg kg(-1)) and 9.8 +/- A 1.4 to 18 +/- A 3.0 mg kg(-1) (average 13.2 +/- A 1.8 mg kg(-1)), for pelargonidin-3-o-glucoside < d.l. and varied from 136 +/- A 19 to 233 +/- A 35 mg kg(-1) (average 185.3 +/- A 28 mg kg(-1)), for malvidin-3-o-glucoside < d.l. and < d.l., respectively.
Keywords: Anthocyanins; Cherry; Cranberry; Optimization; HPLC-ESI-MS